2012
DOI: 10.11138/pr/2012.1.2.073
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in pathophysiology of biliary tree: influence of sex hormones in cholangiocyte growth

Abstract: SummaryCholangiocytes are epithelial cells that line the biliary tree. The intrahepatic biliary tree is characterized by interconnected ducts which starts with canals of Hering, continues into intrahepatic ducts of increasing diameter to end at the level of the extrahepatic bile ducts. These cells play a key role in the ductal secretion of water and bicarbonate during the process of bile formation. These cells are also the target in several chronic cholestatic liver diseases (termed cholangiopathies), includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…suggested that CCA tumours could be consider oestrogen dependent and the use of anti-oestrogen drugs should control the growth of these tumours. 35 …”
Section: Discussionmentioning
confidence: 99%
“…suggested that CCA tumours could be consider oestrogen dependent and the use of anti-oestrogen drugs should control the growth of these tumours. 35 …”
Section: Discussionmentioning
confidence: 99%